THE EFFECT OF WORD WALL IN ENGLISH LEARNING ASSESSMENT FOR EIGHT GRADES AT SMPN 8 TANJUNG JABUNG TIMUR - Corry, Erica; Ervan, Muhammad; Syamsiah, Syamsiah (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2024)
This study investigates the effectiveness of Wordwall, a gamification-based learning media, in improving students' learning outcomes on simple past tense and recount text. Conducted with a single experimental group consisting of 25 eighth-grade students at SMPN 8 Tanjung Jabung Timur, the research employed a pre-experimental design. Data collection involved pre-test and post-test assessments to measure changes in students' comprehension. Over six sessions, students were introduced to Wordwall through interactive activities such as quizzes, word matching, and spinning wheels. Statistical analysis using the independent sample t-test revealed a significant improvement in students' scores, with the mean score increasing from 68.4 on the pre-test to 78.9 on the post-test (t = 5.87, p < 0.05). Before the intervention, only 8 students achieved scores above the minimum passing grade (75), while post-test results showed 21 students surpassing this threshold. The findings underscore Wordwall's potential to enhance student engagement and motivation through gamified elements, effectively addressing learning challenges in traditional methods. The study concludes that Wordwall is a valuable tool for fostering an interactive and enjoyable learning environment, particularly in English language instruction. Future research should explore its application across diverse subjects and educational levels to validate and extend these findings.